The depth geodynamic state and its correlation with the surface geological and geophysical parameters along the sublatitudinal profile of Eurasia - S. Yu. Sokolov (Геодинамика и тектонофизика)
A cross‐sections of longitudinal (P) and transverse (S) wave anomalies (attribute δ(VP/VS)) is constructed along the sublatitudinal profile from the Atlantic Ocean to the Pacific Ocean across the regions of the latest Eurasian volcanism. It is correlated with surface geophysical parameters interpretable in terms of geodynamics: heat flow, seismicity and integrated conductivity of the lithosphere. All the volcanic groups are related to the negative anomalies of S‐ and P‐wave velocity variations at depths, which are observed in the eastern part of the profile from Central Asia to the Pacific Ocean to depths of 1000 km. Such anomalies correlate with the heat flow anomalies and are thus indica‐ tive of a deep source. The absence of deep roots in the western part of the profile from the Caspian to the Western Mediterranean suggests lateral extension of the anomalously ‘hot’ mantle from the Afar branch of the African super‐ plume. The groups of volcanic formations in the Baikal region and the Far East are spatially associated with heat flow anomalies that are three times higher than the background values. A correlation between intraplate volcanism and the lithosphere conductivity suggests the presence of positive anomalies in all volcanic clusters, despite the fact that their background values are considerably different. In the continental part, velocity anomalies are typical of all volcanic groups with positive conductivity anomalies. It is evidenced by seismic tomography that all the volcanic groups (ex‐ cept the Alpine‐Caucasian) have ‘hot’ roots in the upper mantle to depths of 1200 km. The highest maximum conduc‐ tivity values are typical of the zones wherein high intraplate seismicity is absent. Along the profile, there are several zones of high intraplate seismicity, which are separated by aseismic zones or plate boundaries. This suggest the influ‐ ence of the heated state of the mantle and the occurrence of zones of increased conductivity in the lithosphere.